An enantiodivergent synthesis of Cα-methyl nipecotic acid analogues from δ-lactam derivatives obtained through a highly stereoselective cyclization strategy. Issue 21 (1st December 2015) - Banerjee, Souvik; Vogel, Emily R.; Hinton, Daniel; Sterling, Michael; Masterson, Douglas S.
Graphical abstract: Abstract: A stereoselective and enantiodivergent strategy for the construction of δ-lactams is described. The strategy utilizes chiral malonic esters prepared from enantiomerically enriched mono esters of disubstituted malonic acid. A cyclization occurs with the selective displacement of a substituted benzyl alcohol as the leaving group. The resulting δ-lactams are then converted into nipecotic acid analogues using straightforward transformations. The resulting nipecotic acid analogues proved capable organocatalysts in Mannich reactions. Abstract : ( R )-5-(1, 3-Dioxoisoindolin-2-yl)-2-(ethoxycarbonyl)-2-methylpentanoic acid: C17 H19 NO6 [ α ]D 24  = +5.8 ( c 2, MeOH) Source of chirality: Enzymatic Absolute configuration: ( R ) Abstract : ( S )-1-Ethyl 3-(4-nitrobenzyl) 2-(3-(1, 3-dioxoisoindolin-2-yl)propyl)-2-methylmalonate: C24 H24 N2 O8 [ α ]D 23  = −33 ( c 1, CH2 Cl2 ) Source of chirality: the precursor Absolute configuration: ( S ) Abstract : ( R )-Ethyl 3-methyl-2-oxopiperidine-3-carboxylate: C9 H15 NO3 [ α ]D 24  = +29.2 ( c 1, CH2 Cl2 ) Source of chirality: the precursor Absolute configuration: ( R ) Abstract : ( R )-Ethyl 1-benzyl-3-methyl-2-oxopiperidine-3-carboxylate: C16 H21 NO3 [ α ]D 24  = +62.6 ( c 2, CH2 Cl2 ) Source of chirality: the precursor Absolute configuration: ( R ) Abstract : ( S )-Ethyl 1-benzyl-3-methyl-2-thioxopiperidine-3-carboxylate: C16 H21 NO2 S [ α ]D 22  = +75.2 ( c 1, CH2 Cl2 ) Source of chirality: the precursor Absolute configuration: ( S ) Abstract : ( R )-Ethyl 1-benzyl-3-methylpiperidine-3-carboxylate: C16 H23 NO2 [ α ]D 21  = +11.8 ( c 1, CH2 Cl2 ) Source of chirality: the precursor Absolute configuration: ( R ) Abstract : ( R )-1-Benzyl-3-methylpiperidine-3-carboxylic acid: C14 H19 NO2 [ α ]D 22  = +19.0 ( c 1, MeOH) Source of chirality: the precursor Absolute configuration: ( R ) Abstract : ( R )-3-Methylpiperidine-3-carboxylic acid: C7 H13 NO2 [ α ]D 24  = +1.2 ( c 1, MeOH) Source of chirality: the precursor Absolute configuration: ( R ) Abstract : ( S )-3-Methylpiperidine-3-carboxylic acid: C7 H13 NO2 [ α ]D 21  = −1.5 ( c 1, MeOH) Source of chirality: the precursor Absolute configuration: ( S ) Abstract : ( S )-1- tert -Butyl 3-ethyl 2-(3-(1, 3-dioxoisoindolin-2-yl)propyl)-2-methylmalonate: C21 H27 NO6 [ α ]D 23  = −5.2 ( c 1, MeOH) Source of chirality: the precursor Absolute configuration: ( S ) Abstract : ( S )- tert -Butyl 3-methyl-2-oxopiperidine-3-carboxylate: C11 H19 NO3 [ α ]D 23  = −16.2 ( c 1, CH2 Cl2 ) Source of chirality: the precursor Absolute configuration: ( S )